A Modular Biomaterial Scaffold‐Based Vaccine Elicits Durable Adaptive Immunity to Subunit SARS‐CoV‐2 Antigens. Issue 22 (4th October 2021) - Langellotto, Fernanda; Dellacherie, Maxence O.; Yeager, Chyenne; Ijaz, Hamza; Yu, Jingyou; Cheng, Chi‐An; Dimitrakakis, Nikolaos; Seiler, Benjamin T.; Gebre, Makda S.; Gilboa, Tal; Johnson, Rebecca; Storm, Nadia; et al.
Abstract: The coronavirus disease 2019 (COVID‐19) pandemic demonstrates the importance of generating safe and efficacious vaccines that can be rapidly deployed against emerging pathogens. Subunit vaccines are considered among the safest, but proteins used in these typically lack strong immunogenicity, leading to poor immune responses. Here, a biomaterial COVID‐19 vaccine based on a mesoporous silica rods (MSRs) platform is described. MSRs loaded with granulocyte‐macrophage colony‐stimulating factor (GM‐CSF), the toll‐like receptor 4 (TLR‐4) agonist monophosphoryl lipid A (MPLA), and SARS‐CoV‐2 viral protein antigens slowly release their cargo and form subcutaneous scaffolds that locally recruit and activate antigen‐presenting cells (APCs) for the generation of adaptive immunity. MSR‐based vaccines generate robust and durable cellular and humoral responses against SARS‐CoV‐2 antigens, including the poorly immunogenic receptor binding domain (RBD) of the spike (S) protein. Persistent antibodies over the course of 8 months are found in all vaccine configurations tested and robust in vitro viral neutralization is observed both in a prime‐boost and a single‐dose regimen. These vaccines can be fully formulated ahead of time or stored lyophilized and reconstituted with an antigen mixture moments before injection, which can facilitate its rapid deployment against emerging SARS‐CoV‐2 variants or new pathogens. Together, the data show a promising COVID‐19 vaccine candidate and a generally adaptable vaccine platform against infectious pathogens. Abstract : Mesoporous silica rods (MSRs) scaffolds are used as a platform to induce adaptive immunity against SARS‐CoV‐2 antigens. Sustained delivery of GM‐CSF, MPLA, and a variety of SARS‐CoV‐2 subunit immunogens from the MSR vaccine recruite immune cells into the scaffolds and consistently induce antigen‐specific long‐lasting antibodies, cytotoxic T lymphocyte responses (CTL), and viral neutralization in vitro.